Desain Pembelajaran Pendidikan Agama Islam Berbasis Model ADDIE dalam Meningkatkan Kemandirian Belajar - Wulandari, Safira Laila; Fitriani, Siti Khoriah; Neni, Neni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Learning Islamic Religious Education (PAI) requires a systematic and adaptive approach to address the challenges of student development in the modern era. The ADDIE model, which encompasses needs analysis and continuous evaluation, is considered effective in developing PAI learning. This study aims to examine the application of ADDIE-based PAI learning design in enhancing learning independence. The method used is library research by reviewing journals, books, and scientific documents related to the ADDIE model, PAI learning, and learning independence. Data were analyzed using a content analysis approach to identify patterns and relevance between variables. The results show that each stage of the ADDIE model plays a crucial role in strengthening student learning independence, through the design of structured learning activities, interactive media, and evaluations that encourage self-reflection. The implications of this study emphasize the need for consistent application of the ADDIE model by PAI teachers to improve the quality of learning and the formation of independent character. Schools also need to support resources and training for optimal implementation of the ADDIE model.